Cardio-respiratory Events and Inflammatory Response After Primary Immunization in Preterm Infants < 32 Weeks Gestational Age: A Randomized Controlled Study. Issue 10 (October 2017) - Ben Jmaa, Wissal; Hernández, Alfredo I.; Sutherland, Megan R.; Cloutier, Anik; Germain, Nathalie; Lachance, Christian; Martin, Brigitte; Lebel, Marc H.; Pladys, Patrick; Nuyt, Anne Monique
Abstract : Background: Inflammation may depress respiration in neonates. This study aimed to establish a link between postimmunization inflammation and cardio-respiratory events (CREs). Methods: Randomized double-blind controlled study of infants born < 32 weeks gestation receiving the 2 months vaccine, which comprised diphtheria and tetanus toxoids and acellular pertussis adsorbed combined with inactivated poliomyelitis vaccines and Haemophilus b conjugate and the pneumococcal conjugate 10-valent vaccines. Infants were randomized to ibuprofen treatment or a placebo group (n = 28/group). C-reactive protein (CRP) and prostaglandins E2 (PgE2) levels were assessed before and after immunization. CREs were recorded for 72 hours. Heart rate variability was assessed by polysomnography. Results: In the placebo group, immunization was associated with significantly increased CRP levels and an increase in CRE (8.6 ± 11.1 before versus 14.0 ± 12.8 after), which did not reach statistical significance ( P = 0.08), and no change in PgE2. The increase in CRP was correlated with changes in CRE ( r = 0.4: P < 0.05). In the ibuprofen group, immunization significantly increased CRP levels but was not associated with change in CRE (6.7 ± 7.7 before versus 6.8 ± 9.7 after) and PgE2 levels. Comparing the groups, variation in CRE (ΔCRE before versus after immunization) was significantly lower in the ibuprofen group (0.1 ± 7.9 versus 5.4 ± 10.0 ΔCRE; P < 0.05). Conclusion: The first immunization of infants born < 32 weeks was associated with an increase in CRP. Ibuprofen treatment significantly attenuated the variation (Δ) in CRE following first immunization in these infants but the current study could not demonstrate an impact on CRP and PgE2 levels. The impact of anti-inflammatory treatment on antigenicity must be evaluated before their clinical use aiming at reducing CRE after immunization in preterm infants.